Smart contract in construction procurement: insights and recommendations from South Africa - David, Love; Kgomo, Marumo; Aigbavboa, Clinton (Frontiers in Built Environment, 2025)
IntroductionThe traditional procurement system in the construction industry has been plagued by inefficiencies, often serving as a significant obstacle to project delivery. Thus, this study examines the dynamics of adopting smart contracts for project procurement for optimal project success and delivery, with insights and recommendations from the South African Construction Industry.MethodThe study employed a quantitative research approach utilizing descriptive and inferential statistics of Mean Item Score (MIS) and Exploratory Factor Analysis (EFA) for data analysis, based on a purposive sampling technique.ResultsThe MIS results for the benefit, legal & regulatory constraints, and best practices of smart contracts range between 3.73 - 4.41 values, while the Kaiser-Meyer-Olkin (KMO) values were higher than the recommended 0.6 value for the EFA and Cronbach's Alpha value of 0.969 across the indicators.DiscussionThe study's findings revealed two categorized benefits of adopting smart contracts: administrative and operational efficiency of project procurement and procurement optimization; two components of legal and regulatory constraints: Transactional and legal encumbrance to smart contract implementation and legal gaps and ambiguity and two best practices: smart contract reliability practices for project procurement and consistent stakeholders’ engagement for smart contract protocol standardization. The study concludes that Smart contracts can transform global project procurement within the construction industry. The study recommends the development of a green paper on smart contract adoption and integrating smart contracts into standard forms of construction contracts.